HUMOR SUBVERSIF DALAM VIDEO MUSIK BALANCE TON QUOI OLEH ANGELE - Zarkasya, Nur Annisa Khalish; Miranda, Airin (Multikultura, 2025)
The phenomenon of the #MeToo and #BalanceTonPorc hashtags became the focus of attention in various parts of the world in 2017. It was first popularized by Alyssa Milano on her Twitter account using the #MeToo hashtag, and later followed by Sandra Muller with #BalanceTonPorc in France. The feminist movement on social media inspired many artists and musicians, including Angèle, a singer from Belgium. She released a song and music video titled "Balance Ton Quoi" (2019), in which she expressed that the activist spirit of feminism resides within her, turning her song into a feminist anthem. The messages conveyed in her music video are often wrapped in subversive humor. This research aims to demonstrate how subversive humor in the "Balance Ton Quoi" music video can be a form of resistance against sexism. The qualitative research method by Creswell & Poth (2016) is used, focusing on the corpus of Angèle's music video "Balance Ton Quoi." The research draws upon various theories, including Barthes' semiotics (1957) from the book "Mythologies," Kramer's subversive humor (2015), and Scott's notions of public and hidden transcript (1992). Five selected scenes of subversive humor are analyzed, and the results show that the ratio of public to hidden transcript is 2:4. Public transcript is predominantly used not only for educational purposes but also to bring about broader social change, expose injustices, and build solidarity among victims and supporters to attract a larger audience. Moreover, the message must first reach the objects of sarcastic mockery in the music video, namely, adherents of patriarchal ideology, men, and sexual harassers.